(untitled) (Journal of the College of Basic Education, 2022)
he aim of the current research is to know the effectiveness of the Perkins and Blythe model in the achievement and development of critical thinking among fifth-grade literary students in the subject of history. The researcher has two research groups in: the chronological age, the parents’ achievement, the previous achievement, and the critical thinking test, and he identified the scientific material and formulated the behavioral objectives of the educational material, as its number reached (165) behavioral objectives. Of the multiple-choice type with four alternatives, either the second tool was represented by the critical thinking test, which in its final form consisted of (30) items according to the skills identified by Watson and Claser for critical thinking. The results showed that the students of the experimental group who studied according to the Perkins and Blythe model outperformed the students of the control group who studied according to the usual method in the achievement and critical thinking test.